Limited influence of the Agulhas leakage on the Atlantic Meridional Overturning Circulation under present-day climate conditions - Ruize Zhang; Shantong Sun; Zhaohui Chen; Lixin Wu (Communications Earth & Environment)
Abstract The Agulhas leakage is expected to increase as the Southern Hemisphere westerly winds change under climate warming. An increased Agulhas leakage could potentially strengthen the Atlantic Meridional Overturning Circulation (AMOC). To date, however, it remains elusive how much this process could affect the AMOC, which is projected to weaken in the future. Here we carry out a suite of ocean-only simulations, which represent the present climate, and show that an arbitrary 10 Sv increase in the Agulhas leakage strengthens the AMOC by less than 1.3 Sv, which will unlikely substantially offset the projected AMOC weakening. The weak AMOC intensification arises due to compensation between subsurface warming and salinification. However, the AMOC responses to Agulhas leakage increases may depend on the climate background state. Initialized from a collapsed AMOC, which likely occurred during the glacial period, an increased Agulhas leakage can vigorously strengthen the AMOC due to a more unstable AMOC.